Expressão gênica dos REα, REβ e PR em tumores mamários de cadelas por meio do q-PCR - Ramos, R. S. [UNESP]; Avanzi, B. R. [UNESP]; Volpato, R. [UNESP]; Pignaton, W. [UNESP]; Castan, E. P. [UNESP]; Costa, F. A. A. [UNESP]; Lopes, Maria Denise [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2012)
A expressão de receptores de estrógeno (ER) e progesterona (PR) por meio da técnica de q-PCR foi avaliada em 26 cadelas portadoras de neoplasias mamárias e cinco cadelas sem afecções mamárias (grupo controle). Os resultados mostraram que os três grupos de animais estudados - com tumor maligno ou benigno e controle - expressaram receptores de estrógeno alfa, beta e progesterona. A quantificação relativa mostrou tendência para uma expressão maior de receptores no grupo controle e menor no grupo de animais com neoplasias malignas. Além disso, observou-se expressão maior de ERα em relação ao ERβ, e as neoplasias malignas de origem mista apresentaram maiores concentrações dos receptores PR, ERα e ERβ que as neoplasias de origem epitelial.

The estrogen and progesterone receptor (ER and PR) expression with the q-PCR technique was evaluated in 26 female dog carrying of mammary tumors and five female dogs without mammary disease (control group). The results showed that the three animal groups evaluated - malignant or benign tumor and control - expressed alpha and beta estrogen and progesterone receptors. The relative quantification showed a tendency for a higher expression of receptors from the control group and smaller in the malignat tumors animal group. Also, there was a major ERα expression regarding to ERβ and the malignat tumors from mixed origin presented higher concentrations of receptors PR, ERα and ERβ, when compared to tumors of epithelial origin.
REα, REβ and PR gene expression in mammary gland tumors of female dogs by q-PCR
Keywords: cadela; neoplasia mamária; estrógeno; progesterona; receptores; female dogs; mammary gland tumor; estrogen; progesterone; receptors